Headaches in the emergency department –a survey of patients’ characteristics, facts and needs - Doretti, Alberto; Shestaritc, Irina; Ungaro, Daniela; Lee, John-Ih; Lymperopoulos, Loukas; Kokoti, Lili; Guglielmetti, Martina; Mitsikostas, Dimos Dimitrios; Lampl, Christian (Journal of headache and pain, 2019)
Background and aim Headache is very often the cause for seeking an emergency department (ED). However, less is known about the different diagnosis of headache disorders in the ED, their management and treatment. The aim of this survey is to analyse the management of headache patients in two different ED in Europe. Methods This retrospective survey was performed from September 2018 until January 2019. Patients were collected from the San Luca Hospital, Milan, Italy and the Ordensklinikum Barmherzige Schwestern, Linz, Austria. Only patients with a non-traumatic headache, as the primary reason for medical clarification, were included. Patients were analysed for their complexity and range of examination, their diagnoses, acute treatment and overall efficacy rate. Results The survey consists of 415 patients, with a mean age of 43.32 (SD ±17.72); 65% were female. Technical investigation was performed in 57.8% of patients. For acute treatment non-steroidal-anti-inflammatory drugs (NSAIDs) were the most used, whereas triptans were not given. A primary headache disorder was diagnosed in 45.3% of patients, being migraine the most common, but in 32% of cases the diagnosis was not further specified. Life-threatening secondary headaches accounted for less than 2% of cases. Conclusions The vast majority of patients attending an ED because of headache are suffering from a primary headache disorder. Life-threatening secondary headaches are rare but seek attention. NSAIDs are by far the most common drugs for treating headaches in the ED, but not triptans.